A cold plasma jet accelerates wound healing in a murine model of full‐thickness skin wounds. Issue 2 (February 2017) - Schmidt, Anke; Bekeschus, Sander; Wende, Kristian; Vollmar, Brigitte; von Woedtke, Thomas
Abstract: Cold plasma has been successfully applied in several fields of medicine that require, for example, pathogen inactivation, implant functionalization or alteration of cellular activity. Previous studies have provided evidence that plasma supports the healing of wounds owing to its beneficial mixtures of reactive species and modulation of inflammation in cells and tissues. To investigate the wound healing activity of an atmospheric pressure plasma jet in vivo, we examined the cold plasma's efficacy on dermal regeneration in a murine model of dermal full‐thickness ear wound. Over 14 days, female mice received daily plasma treatment. Quantitative analysis by transmitted light microscopy demonstrated a significantly accelerated wound re‐epithelialization at days 3–9 in comparison with untreated controls. In vitro, cold plasma altered keratinocyte and fibroblast migration, while both cell types showed significant stimulation resulting in accelerated closure of gaps in scratch assays. This plasma effect correlated with the downregulation of the gap junctional protein connexin 43 which is thought to be important in the regulation of wound healing. In addition, plasma induced profound changes in adherence junctions and cytoskeletal dynamics as shown by downregulation of E‐cadherin and several integrins as well as actin reorganization. Our results theorize cold plasma to be a beneficial treatment option supplementing existing wound therapies.